N-Cinnamoylation of Antimalarial Classics: Quinacrine Analogues with Decreased Toxicity and Dual-Stage Activity - Gomes, Ana
Plasmodium falciparum, the causative agent of the most lethal form of malaria, is becoming increasingly resistant to most available drugs. A convenient approach to combat parasite resistance is the development of analogues of classical antimalarial agents, appropriately modified in order to restore their relevance in antimalarial chemotherapy. Following this line of thought, the design, synthesis and in vitro evaluation of N-cinnamoylated quinacrine surrogates, 9-(N-cinnamoylaminobutyl)amino-6-chloro-2-methoxyacridines, is reported. The compounds were found to be highly potent against both blood-stage P. falciparum, chloroquine-sensitive 3D7 (IC50 = 17.0-39.0 nm) and chloroquine-resistant W2 and Dd2 strains (IC50 = 3.2-41.2 and 27.1-131.0 nm, respectively), and liver-stage P. berghei (IC50 = 1.6-4.9 mm) parasites. These findings bring new hope for the possible future \"rise of a fallen angel\" in antimalarial chemotherapy, with a potential resurgence of quinacrine-related compounds as dual-stage antimalarial leads.